Implementasi Slogan Badan Bahasa Utamakan Bahasa Indonesia, Lestarikan Bahasa Daerah, Dan Kuasai Bahasa Asing di AM Educenter, Depok, Jawa Barat - Ahmad Khoiril Anam; Hilaliyah, Hilda; Ismail Bambang Subianto; Muhammad Dandi (Keris: Journal of Community Engagement, 2024)
The existence of Indonesian language needs to be promoted. This is in line with the slogan of Utamakan Bahasa Indonesia, Lestarikan Bahasa Daerah, dan Kuasai Bahasa Asing. However, in reality, the implementation related to the slogan of the Language Agency has not been fully implemented in AM Educenter RT 01, RW 03, Meruyung, Limo, Depok, West Java. The solution offered is that the Implementation Team provides an alternative implementation of the slogan Utamakan Bahasa Indonesia, Lestarikan Bahasa Daerah, dan Kuasai Bahasa Asing in the form of posters and the like which are installed at AM Educenter as a form of love for Indonesian. The method used in the implementation of community service is face-to-face (offline) by complying with health protocols. The results achieved are the creation of understanding in partners regarding the implementation of the slogan Utamakan Bahasa Indonesia, Lestarikan Bahasa Daerah, dan Kuasai Bahasa Asing and the installation of posters as a form of implementation of the slogan.